Development of spontaneous synaptic activity in a hypothalamic network grown in culture - Swandulla, Dieter; Misgeld, Ulrich (Journal of basic and clinical physiology and pharmacology, 1990)
Der Artikel Development of spontaneous synaptic activity in a hypothalamic network grown in culture wurde am 1. Januar 1990 in der Zeitschrift Journal of Basic and Clinical Physiology and Pharmacology (Band 1, Heft 1-4) veröffentlicht.
Gesehen am 08.04.2021